1997
DOI: 10.1006/bbrc.1997.7007
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Carrier Protein X (SCPx) Is a Peroxisomal Branched-Chain β-Ketothiolase Specifically Reacting with 3-Oxo-pristanoyl-CoA: A New, Unique Role for SCPx in Branched-Chain Fatty Acid Metabolism in Peroxisomes

Abstract: cholesterol in microsomes and also the acyltransferase One of the most important functions of peroxisomes, mediated esterification of intracellular cholesterol [1]. at least in humans, is the b-oxidation of a range of Moreover, in steroid hormone producing cells SCP2 is different fatty acids and fatty acid derivatives. Recent thought to facilitate the transport of cholesterol to mistudies have shown that the enzymatic machinery re-tochondria, where the first committed step in the forquired for the b-oxidations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…2) we hypothesize that IpfD and E are responsible for the acid side chain removal based on the role that related proteins play in acyl group transfer (Fig. 4) (Bangera & Thomashow, 1999;Kube et al, 2004;Kühner et al, 2005;Leuthner & Heider, 2000;Verhoeven & Jakobs, 2001;Wanders et al, 1997;Westin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) we hypothesize that IpfD and E are responsible for the acid side chain removal based on the role that related proteins play in acyl group transfer (Fig. 4) (Bangera & Thomashow, 1999;Kube et al, 2004;Kühner et al, 2005;Leuthner & Heider, 2000;Verhoeven & Jakobs, 2001;Wanders et al, 1997;Westin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed molecular analyses of mammalian SCPx family members have demonstrated their involvement in two specific metabolic reactions in eukaryotes, namely bile-acid synthesis (Takeuchi et al, 2004) and the b-oxidation of pristanoyl-CoA, a branchedchain fatty acid (Fig. 5) (Verhoeven & Jakobs, 2001;Wanders et al, 1997;Westin et al, 2007). In both cases, SCPx is specifically involved in the b-oxidation of an amethyl b-keto fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the SCP-x protein indicate that along with its inherent ability to transport lipids such as cholesterol (16), this protein has unique roles in the peroxisomal ␤ -oxidation of branched-chain fatty acids and in bile acid formation from cholesterol (17)(18)(19)(20). Although in vitro experiments show that SCP-x has the same substrate specificity for straight-chain fatty acids as that of the conventional peroxisomal thiolases, SCP-x also has a unique ability to catalyze the thiolytic cleavage of 3-oxoacyl-CoA esters of branched-chain molecules with methyl groups at the 2-position, such as pristanic acid (17,19,21) and cholestanoic acid (22).…”
mentioning
confidence: 99%
“…With respect to their physiological role, it is now clear that the D-specific enzyme as encoded by HSD17B4 catalyzes the hydration and subsequent dehydrogenation of most peroxisomal beta-oxidation substrates including the enoyl-CoA esters of VLCFAs, pristanic acid and DHCA and THCA, whereas the L-specific enzyme appears to handle the dicarboxylic enoylCoA esters specifically (see Figure 4; Houten et al, 2012). Finally, with respect to the two thiolases, work on the isolated enzymes (Antonenkov et al, 1997;Wanders et al, 1997) as well as Sterol Carrier Protein X (SCPx)-deficient patients (Ferdinandusse et al, 2006) and mutant mice (Seedorf et al, 1998;Kannenberg et al, 1999) has shown that both peroxisomal 3-ketoacyl-CoA-thiolase 1 (ACAA1; pTH1) and SCPx (pTH2) encoded by ACAA1 and SCP2, respectively, are involved in the oxidation of VLCFAs, whereas the 3-ketoacyl-CoA esters of pristanic acid, DHCA and THCA are solely cleaved by SCPx. The redundancy of the two thiolases with respect the oxidation of VLCFAs may explain why peroxisomal 3-ketoacyl-CoA-thiolase1 (ACAA1)-deficiency has not been identified sofar.…”
Section: (B) Fatty Acid Beta-oxidationmentioning
confidence: 99%